Implementation of Integrated Marketing Communication on Low Cost Carrier Airlines in the New Normal Era (Qualitative Descriptive Study at PT Citilink Indonesia Branch Office Denpasar) - Cristina, Ni Putu Candra; Arie Yudhistira, Putu Gde; Evi Wijayanti, Ni Putu (Jurnal Penelitian Pariwisata, 2022)
This study aimed to determine how the implementation of integrated marketing communications at PT Citilink Indonesia Denpasar Branch Office as a low-cost airline in the new normal era. The research method used in this study is a qualitative descriptive method with data collection methods through observation, interviews, and documentation. The results of this study are based on five dimensions of integrated marketing communication, showing that 1) advertisements at the PT Citilink Denpasar Branch Office use the company's digital on-channels such as Instagram, Facebook, Twitter, and Youtube; 2) The company's direct & digital marketing is done through the website, mobile app & call center; 3) Sales promotions are channeled through social media and websites that offer promotions for free rapid tests, snacks & drinks, internet quota, round-trip tickets, and discounted stays; 4) Public relations is carried out through online media relations by providing positive news that helps maintain the company's brand image. 5) Personal Selling at the PT Citilink Indonesia Denpasar Branch Office is done through ticket sales counters at Ngurah Rai Airport. Keywords: Customer Loyalty, Brand Image, Brand Trust